Bearing God's name why Sinai still matters - Imes, Carmen Joy 1977- (Downers Grove, IL InterVarsity Press, 2019)
"What does the Old Testament-especially the law-have to do with your Christian life? In this warm, accessible volume, Carmen Joy Imes takes readers back to Sinai, arguing that we've misunderstood the command about "taking the Lord's name in vain." Instead, Imes says that this command is really about "bearing God's name," a theme that continues throughout the rest of Scripture"--
Becoming the people who bear God's name: Leaving Egypt: Deliverance as grace -- Surprised at Sinai: Law as gift -- Major deal: Covenant as vocation -- Now what? Appointed for service -- Ready to roll: Prepared for the promised land -- Living as the people who bear God's name: Striking out: From Mount Sinai to Mount Zion -- What Yahweh sees: The faithful few -- Just give me Jesus: The gospel witness -- Blob tag: The mission of Jesus -- Who let you in? Gentiles and the mission of God -- Conclusion.
Includes bibliographical references and index
Keywords: Bible -- Criticism, interpretation, etc; Bible; Image of God; Identification (religion); Identity (Psychology) -- Religious aspects -- Christianity; Identity (Philosophical concept) -- Religious aspects -- Christianity; Identification (religion); Identity (Psychology) ; Religious aspects ; Christianity; Image of God; Criticism, interpretation, etc